Standard Time and Workload of Pharmacists in Medication Reconciliation Service for In-patients, Chiangkham Hospital, Phayao - Ngamsom, Panadda; Chumkamleu, Roongnapa (Journal of Health Science of Thailand, 2017)
This study was a cross-sectional descriptive study aimed to determine the standard time and workload of pharmacists carrying out medication reconciliation service at in-patient department, Chiangkham Hospital and to assess pharmacist manpower required for the service by using work sampling technique and stopwatch time study. The study was conducted at in-patients department, Chiangkham hospital, Phayao during July 1 to October 31, 2012. Total of 1,408 patients were included into this study. The study’s findings demonstrated that the standard times for creating complete medication list, checking for medication reconciliation, monitoring for the intervention and checking for medication reconciliation at discharge were 6.11, 4.06, 3.18 and 1.19 minutes, respectively. The total standard time of pharmacists in providing medication reconciliation service was 14.54 minutes per patient. The workload of pharmacists for providing medical reconciliation service at in-patient department was 957.5 man-hours per year for a total of 3,951 patients. Therefore, medication reconciliation can be served at in-patient department by at least 0.56 pharmacist. In the other word, providing medication reconciliation service at in-patient department, Chiangkham Hospital required less than one pharmacist. In conclusion, under well-planned system medication reconciliation can be integrated to other pharmaceutical care services with no need to increase pharmacist manpower. To decrease amount of time spent in the process, integrated system and multidisciplinary teamwork are required.